2020
DOI: 10.3390/plants9101397
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Responses of Phenolic Compounds and Immobilization of Copper in Imperata cylindrica, a Plant with Potential Use for Bioremediation of Cu Contaminated Environments

Abstract: This work examined the capability of Imperata cylindrica to respond, tolerate and accumulate Cu when growing at high Cu concentration (300 mg kg−1 of substrate) at different times of exposure (2, 14 and 21 days). The Cu accumulation in plants was examined by atomic absorption spectroscopy (AAS) and Cu localized by Scanning Electron Microscopy-Energy Dispersive X-Ray spectroscopy. Additionally, the phenolic compound identifications and concentrations were determined using liquid chromatography coupled to mass s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 53 publications
2
11
1
Order By: Relevance
“…This also supports the further homogeneity in the shoot samples irrespective of the Cu treatment ( Figure 2 and Figure 3 ). These results are in agreement with previous report by Vidal et al [ 20 ], where high concentrations of Cu (> 300 mg kg −1 DW) were reported in root organs of I. cylindrica , compared to values about 10-fold lower in shoot tissues. The Cu uptake and accumulation firstly occurs at a great magnitude in the root organs, therefore producing a low rate of translocation to shoots [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…This also supports the further homogeneity in the shoot samples irrespective of the Cu treatment ( Figure 2 and Figure 3 ). These results are in agreement with previous report by Vidal et al [ 20 ], where high concentrations of Cu (> 300 mg kg −1 DW) were reported in root organs of I. cylindrica , compared to values about 10-fold lower in shoot tissues. The Cu uptake and accumulation firstly occurs at a great magnitude in the root organs, therefore producing a low rate of translocation to shoots [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 94%
“…The Probable copper-transporting ATPase HMA5, in turn, plays a key role in transmembrane Cu transport and is specifically induced by Cu in plants [50]. Moreover, studies in Oryza sativa demonstrated that this gene is involved in the loading of Cu to the xylem in roots and other organs [51], playing a key role in the Cu accumulation in root organs, which agrees with other observations by Vidal et al [20]. The joint up-regulation of these genes demonstrated their importance in the Cu detoxification process in the plant roots, since these transporters take Cu ions from the soil, further distributing among plant organs and finally compartmentalize into subcellular organelles in the cell [52].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our data suggest that these strategies are involved with protection against oxidative damage, thus protection of the photosynthetic machinery. Previous investigations [ 55 ] have also confirmed that plants that produce high amounts of phenolic compounds as a response to the heavy metal stress could be good candidates for phytoremediation.…”
Section: Discussionmentioning
confidence: 82%